Filmes publicitários: o processo de criação e as buscas do mercado global - Bertomeu, João Vicente Cegato (2008)
The research aims to study the creating process of advertising movies in order to identify and to go in-depth of their specificities as well as in the colective process involving customer, agency and production firm. The study also strives to understanding the process involving conception and production when a persuasive communication takes place globally. The concept and fundamentals of the construction of the hibrid culture as well as its role in the advertising discourse will be analysed. The conception will be analysed from the view of the companies - in the marketing aspects of the agencie´s creative people - as well as in the persuasive search of the world language and the producer firm - in the technical aspects of the production. We use the genetic criticism as methodology and processual documents of advertising campaings developed by relevant agencies based in Sao Paulo (AlmapBBDO, JWThompson, MatosGrey, DPZ, Neogama, McCann Erickson, DM9DDB) were selected. Interviews and professional testimonials of those involved in the conception process of those campaigns were used. Concerning the theoretical framework, the theory of conception based on semiotics was used. The following authors were quoted in terms of theories of conception and creativity: Kotler and Armstrong, for the conception in the creating and creative process: Salles and Ostrower and regarding the matters of international business and global communication: Keegan and Levitt. The audiovisual language was used with the support of : Comparato, Aumont e Carriére; in the especificities of the advertising language: Vestergaard and Sodré; and culture, semiosphere, hibridization and global communication: Morin, Lotman, Martín-Barbero, Pinheiro, Canclini and Mattelart, respectively. In the final discussion, it was used the conception of global advertising movies in a creative process as a process net, extensively collective, complex and dynamic, developed by a multi-knowledge professionals who seek to achieve a global audience together